2015
DOI: 10.1088/1674-1056/24/2/027503
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferromagnetism with high magnetic moment in Cu-doped AlN single crystal whiskers

Abstract: Ferromagnetism is investigated in high-quality Cu-doped AlN single crystal whiskers. The whiskers exhibit room-temperature ferromagnetism with a magnetic moment close to the results from first-principles calculations. High crystallinity and low Cu concentrations are found to be indispensable for high magnetic moments. The difference between the experimental and theoretical moment values is explored in terms of the influence of nitrogen vacancies. The calculated results demonstrate that nitrogen vacancies can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The slight red shift of E 2 (high), A 1 (TO), and A 1 (LO) of the AlN:Cu NRs relative to those of the undoped AlN NRs is ascribed to the disorder of the crystals resulted from the incorporation of Cu. Similar observation in AlN:Sc six-fold symmetrical hierarchical nanostructures, [27] AlN:Cu whiskers, [195] and GaN:Si NWs [196] are provided in Figure 14(b)-(d).…”
Section: Raman Scatteringsupporting
confidence: 81%
See 1 more Smart Citation
“…The slight red shift of E 2 (high), A 1 (TO), and A 1 (LO) of the AlN:Cu NRs relative to those of the undoped AlN NRs is ascribed to the disorder of the crystals resulted from the incorporation of Cu. Similar observation in AlN:Sc six-fold symmetrical hierarchical nanostructures, [27] AlN:Cu whiskers, [195] and GaN:Si NWs [196] are provided in Figure 14(b)-(d).…”
Section: Raman Scatteringsupporting
confidence: 81%
“…AlN:Cu NRs, [193] (b) AlN:Sc six-fold symmetrical hierarchical nanostructures, [27] (c) AlN:Cu whiskers, [195] and (d) GaN:Si NWs. [196]…”
Section: Raman Scatteringmentioning
confidence: 99%
“…Experimental and theoretical studies showed that Cu doped AlN nanorods, films, and powders exhibit room temperature ferromagnetism. [29][30][31][32] In addition, it was predicted experimentally that Zn can be incorporated into an AlN solid solution, [33] and correspondingly, it has been confirmed theoretically that Zn/Cd doping can induce magnetism in an AlN nanosheet. [34] To date, in contrast with the wide study of the electronic structure and magnetic properties of doped monolayer AlN, the effects of group 1A and group 2A dopants in monolayer AlN have not been investigated.…”
Section: Introductionmentioning
confidence: 85%
“…[22] Meanwhile, some experimental and theoretical results have also been reported that the Cu-doped AlN films exhibit roomtemperature ferromagnetism. [28][29][30][31][32] On the other hand, compared with conventional transition metal dopants, the nonmagnetic dopants have been a hot topic in recent years due to their high-temperature magnetism, which may be conducive to the mushroom growth of the spin electronics. To date, notwithstanding the magnetism in AlN nanosheets has been widely considered, a detailed understanding of the induced magnetism in Zn/Cd-doped AlN nanosheets has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%